Advanced immunostaining approaches to study early male germ cell development - Bryan A. Niedenberger; Christopher B. Geyer (Stem Cell Research, 2018)
Mammalian male germ cell development takes place in the testis under the influence of a variety of somatic cells and an incompletely defined paracrine and endocrine influences. Since it is not recapitulated well in vitro, researchers studying spermatogenesis often manipulate the germline by creating transgenic or knockout mice or by administering pharmaceutical agonists/antagonists or inhibitors. The effects of these types of manipulations on germline development can often be determined following microscopic imaging, both of stained and immunostained testis sections. Here, we describe approaches for microscopic analysis of the developing male germline, provide detailed protocols for a variety of immunostaining approaches, and discuss transgenic fluorescent reporter lines for studying the early stages of spermatogenesis. Keywords: Prospermatogonia, Spermatogonia, Testis, Immunofluorescence, Immunohistochemistry